Desiccation resistance traits predict freshwater invertebrate survival and community response to drought scenarios in a Neotropical ecosystem. (December 2020) - Céréghino, Régis; Françoise, Léa; Bonhomme, Camille; Carrias, Jean-François; Compin, Arthur; Corbara, Bruno; Jassey, Vincent; Leflaive, Joséphine; Rota, Thibaut; Farjalla, Vinicius; Leroy, Céline
Highlights: Median lethal time (LT50) is a measure of sensitivity to desiccation stress. LT50 of tropical freshwater invertebrates ranged from 4.18 to 19.06 days. LT50 is predicted by desiccation-resistance traits, cuticle content and dry body mass. LT50 predicts community response to various drought intensities in nature. Abstract: The intensification of dry seasons is a major threat to freshwater biodiversity in Neotropical regions. Little is known about resistance to drying stress and the underpinning traits in Neotropical freshwater species, so we don't know whether desiccation resistance allows to anticipate shifts in biological diversity under future climate scenarios. Here, we used the aquatic invertebrates that live in the rainwater-filled leaves of tank bromeliads, to examine the extent to which desiccation resistance of species measured in the laboratory predicts community response to drought intensification in nature. We measured desiccation resistance in 17 invertebrate species (>90% of the biomass usually found in bromeliads of French Guiana) by recording the median lethal time (LT50) of experimental populations exposed to controlled conditions of residual moisture. In the field, we placed rainshelters above tank bromeliads to emulate drought scenarios ranging from the ambient norm to IPCC scenarios and extreme events, and we recorded the response of functional community structure. LT50 ranged from 4.18 to 19.06 days, and was related to cuticle content and dry body mass. Among other functional indicators that represent strategies to optimize resource use under stressful conditions (e.g., habitat use, trophic specialization), LT50 was the best predictor of community structure responses along a gradient of emulated drought intensities. Therefore, species' LT50s measured under laboratory conditions can be used to forecast aquatic community response to drying stress in nature. Anticipating how species will cope with drought has never been more important for environmental managers to support climate change adaptation. We show that desiccation resistance in freshwater invertebrates is a key indicator of potential population size and local–global range shifts, and this could be especially true in the Neotropics where species have narrow physiological tolerances for climatic variation.